2010
DOI: 10.3109/00016481003785994
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic visual acuity during head-thrust test in canal planes in healthy subjects and patients with vestibular neuritis

Abstract: The htDVA was reliable in normal subjects (intra-class correlation coefficient (ICC) = 0.44-0.71; p = 0.001-0.007). The htDVA score showed an age-dependent increase for all canals (p < 0.0001). The 95th percentile of htDVA was used as the criterion to consider htDVA as abnormal in patients with VN. In all, 44%, 30%, and 16% of patients had an increase in htDVA score for one, two or all three canals on the affected side. The sensitivity and specificity of the htDVA test for the horizontal canal were 22% and 85%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Age has previously been related to poorer active DVA in individuals regardless of degree of vestibular loss (i.e., normal, unilateral or bilateral peripheral vestibular involvement) (8;11;13;18). Likewise, Viciana et al (19) also demonstrated that htDVA significantly worsens with age. Schubert et al (5) originally proposed that htDVA scores falling outside 0.158 LogMAR (mean + 2 SD in normal controls, n = 19) be considered the cut off for pathologically abnormal htDVA.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Age has previously been related to poorer active DVA in individuals regardless of degree of vestibular loss (i.e., normal, unilateral or bilateral peripheral vestibular involvement) (8;11;13;18). Likewise, Viciana et al (19) also demonstrated that htDVA significantly worsens with age. Schubert et al (5) originally proposed that htDVA scores falling outside 0.158 LogMAR (mean + 2 SD in normal controls, n = 19) be considered the cut off for pathologically abnormal htDVA.…”
Section: Discussionmentioning
confidence: 89%
“…Schubert et al (5) originally proposed that htDVA scores falling outside 0.158 LogMAR (mean + 2 SD in normal controls, n = 19) be considered the cut off for pathologically abnormal htDVA. However, this htDVA cutoff is likely inappropriate for normal individuals over the age of 60 as the 95 th percentile reference value projected by Viciana et al (19) ranges from 0.230 – 0.330 LogMAR. Our findings continue to support that visual acuity performance is dependent on age, and that age-based normative data are necessary for determining a diagnostic cutoff, particularly for individuals greater than 60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of the angular VOR in response to yaw stimuli of 60 to 100°/s found responses in subjects older than 75 years to be 89% of the response of people age 18 to 39, but the difference was not significant (Baloh et al 1993). Dynamic visual acuity with head rotation, which is test of the angular VOR as well as vision, also declines with age (Viciana et al 2010). Thus, although angular VOR function declines with age, the decline is small compared with that seen in the LVOR and VEMP.…”
Section: The Effect Of Agingmentioning
confidence: 99%
“…Size of the smallest optotype displayed varies across studies and may also contribute to reliability. In the current study, the smallest optotype displayed was 20/ 10 (consistent with NIH DVA protocol; 10), whereas some previous studies have limited the smallest optotype to 20/20 (6,7,16). Another difference between studies is the distance at which the test was administered.…”
Section: Reliabilitymentioning
confidence: 70%
“…Furthermore, active head movements reflect some activities of daily living (e.g., looking both ways to cross a street). This testing paradigm has been used across several studies examining DVA (e.g., [6][7][8][9][10][11]20); whereas other studies have used a nonvolitional (passive) head movement for assessment of DVA (16,25,26). The ability to preprogram eye movements for gaze stability is different for active versus passive head movements; thus, comparison of the current study's results is limited to studies using active head movements.…”
Section: Limitationsmentioning
confidence: 99%